Journey into Islam the crisis of globalization - Ahmed, Akbar S.; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2007)
"Presents a tour of Islam and its peoples as it follows author's anthropological expedition to the three major regions of the Muslim world--the Middle East, South Asia, and East Asia. Reveals unique information on large, often misunderstood populations, describing the experiences and perceptions of ordinary Muslims, women, and youth"--Provided by publisher.
An anthropological excursion into the Muslim world -- The struggle within Islam -- Tribes, women, and honor in the age of globalization -- Who is defining Islam after 9/11 and why? -- The clash of civilizations? -- Lifting the veil -- Epilogue: the hope of the world.
Includes bibliographical references (p. 287-301) and index.
Electronic reproduction.
Keywords: Religious awakening -- Islam; Islam -- 21st century; Globalization -- Religious aspects -- Islam; Islamic renewal -- Islamic countries; Islamic countries -- Description and travel; Electronic books